The challenges of global competition : Malaysian SMEs and AFTA / Saadiah Mohamad, Rohani Mohd and Mazzini Muda - Mohamad, Saadiah; Mohd, Rohani; Muda, Mazzini (Research Management Institute (RMI), 2008)
ASEAN Free Trade Area or AFTA manifests market liberalization; it may present significant opportunities or may pose significant threats to SMEs in Malaysia. The main purp ose of this study is to identify the challenges and impact of AFTA on SMEs :~ business operations. Specifically, the aim is to assess the level ofawareness of AFTA among SMEs in Malaysia and to explore the relationship between managers' perceptions of AFTA and the strategies employed as well as their intending business operational changes. Data from 273 firms were used based on questionnaires distributed to SMEs of various sectors in the four regions in West Malaysia: Northern (Kedah, Penang and Perak ), Western (Klang Valley) , Eastern (Terengganu) and Southern (Johor). The findings indicate that only slightly more than half of the managers surveyed were aware of AFTA and its implications. The findings also exhibit that managers' perceptions of AFTA are related positively to differentiation and cost leadership strategy and besides employing the relevant strategy, those who have more favorable perceptions of AFTA are more likely to carry out changes in business operations that will enhance their export activities to ASEAN countries.